The devil is a part-timer! 12 - Wagahara, Satoshi (Yen Press, 2018)
"MgRonald is closed for renovations, which means the Devil King is temporarily out of a job. His hunt for employment takes him all the way to the Nagano prefecture where he'll get a taste of agricultural life. Can Maou survive his time in the sticks, or is he simply too city spoiled?"--Publisher marketing.